The implementation of ring oscillator based PUF designs in Field Programmable Gate Arrays using of different challenge - Avaroğlu, Erdinç (Physica A, 2020)
Physically Unclonable Functions (PUFs) are the components of integrated circuits that produce sign, peculiar to each chip, based on the uncontrollable processes that occur during integrated circuit manufacture. There are various use areas of Physically Unclonable Functions circuits such as authentication, key generation and random number generation. Secure key generation in cryptography depends on the fact the random numbers produced are true random numbers. There are numerous methods to generate true random numbers such as thermal noise, anthropogenic interactions and ring oscillator. In order to use the random numbers produced in the article in the field of cryptography, a random number generator based on a ring oscillator (RO)-based Physically Unclonable Functions has been used in an Field Programmable Gate Array environment. Challenges that have periodic and non-periodic structures are used with the aim of increasing the randomness of acquired random numbers and preventing the attacks that Physically Unclonable Functions are exposed to. The statistical qualities of responses produced by these challenges are examined. The responses produced were subject to a statistical test (NIST), a statistical complexity measure (SCM), auto correlation and scale index. The statistical test results shows that the proposed system produces successful results. •A RNG based on a ring oscillator (RO)-based PUF has been used in an FPGA environment.•Periodic and non-periodic structures were used as a challenge.•The tests applied are NIST, SCM autocorrelation tests and scale index.